An Assessment of the Productivity and Effectiveness of Law Making from the Legal Perspective of the Indonesian State - Arifin, Firdaus (International Journal of Law and Public Policy (IJLAPP), 2024)
The People's Representative Council of the Republic of Indonesia (DPR RI) plays a crucial role in the legislative process that shapes national policies. However, its effectiveness is often questioned due to discrepancies between the number of enacted laws and the set targets. This study aims to evaluate the legislative performance of the DPR RI during the 2019-2024 period, focusing on the quality and relevance of the laws produced. The research employs a normative approach to assess the alignment of legislative outputs with constitutional principles, alongside an empirical approach to measure legislative productivity and its impact on society. The findings indicate that although the DPR RI successfully enacted several laws, many of these legislative products fall short of public expectations in terms of both quantity and quality. The implications of this study highlight the need for improved legislative efficiency and increased public participation to ensure that the laws produced are more responsive to societal needs.